Investigating microplastics and potentially toxic elements contamination in canned Tuna, Salmon, and Sardine fishes from Taif markets, KSA - Hussien Nahed Ahmed (De Gruyter, 2021)
Microplastics (MPs) have been documented in different foodstuffs and beverages, that could affect human health due to their ingestion. Furthermore, seafood contamination with MPs puts pillars of food availability and utilization at risk. The present study investigates MPs and toxic elements pollution in commercially canned fishes from Taif governorate markets. Seven different canned fishes’ brands were used in the present study from different manufacturer countries and purchased from Taif markets. Tissue samples were digested by 10% of KOH; then, dry filters were analyzed by Fourier-transform infrared spectroscopy to detect MPs. Filtrates were used to detect any potentially toxic elements by inductively coupled plasma. Different MPs were detected in edible tissue, such as canned Tuna contaminated with nylon, 1,2-polybutadiene, and ethylene vinyl alcohol. Sardines contain ethylene vinyl alcohol and poly(vinyl stearate), but Salmon does not have any MPs. Different elements were present in the selected samples in the decreasing order of Al > Se > Zn and traces of As and Sb. Canned fishes were contaminated with MPs and potentially toxic elements. This contamination could be a warning of the potential health risks with the long-term exposure. Therefore, it is recommended to include micro-, meso-, and even nanoplastics in the guidelines of testing food safety management systems.